Uso da vermiculita na adsorção do corante vermelho reativo BF – 4B e do óleo presente em água produzida sintética - Mota, Amyllys Layanny Fernandes (Universidade Federal Rural do Semi-Árido, 2018)
Petroleum is one of the most important sources of energy in the world, besides being raw material for the production of diverse fuels, it has become essential to the facilities and amenities of modern life. As a consequence of the technological advance of the oil industry, environmental problems have intensified, and one of them is the disposal of waste generated from the prospecting process to the production process, one of which is water produced and considered to be of greatest concern. produced. Because natural resources are depletable, conscious use is needed to achieve expected business results and reduce environmental impacts. This work studies the vermiculite for use as an adsorbent in the process of adsorption in synthetic water and with the reactive red dye BF-4B, in order to remove the contaminants present in the water, where analyzes were performed with washed vermiculite and not washed in the experiments performed with synthetic produced water, and the results showed that for the washed material the adsorption process did not occur due to its internal structure being filled with water. For the experiments performed with the reactive red dye BF-4B, the washed, unwashed, washed and crushed vermiculite was used, the satisfactory results were for the washed material and the crushed washing, where in the washed the best results were for the larger ones granulometry because its particles were larger, dried faster, and in the shredded wash, the best results were with the smallest particle sizes, at the moment of grinding, the agglomerated particles were separated and thereby increased the surface area.
Monografia
Keywords: Água Produzida; Adsorção; Petróleo; Vermiculita; Produced Water; Adsorption; Petroleum; Vermiculite; ENGENHARIAS::ENGENHARIA DE PETROLEO